Que luxo é esse brinde!: uma investigação sobre marcas masstige e ações promocionais - Silva, Daiane Estevão Arcanjo da (2022)
With the growth of the population's income levels, driven by the strengthening of the economy of emerging countries and the desire of these consumers to enjoy the prestige that luxury has, companies saw an opportunity to expand their business, with the emergence of the masstige segment, that combines the prestige of luxury brands with a more affordable price. In Brazil, some masstige brands glimpsed in promotional actions the possibility of expanding their market even more, generating brand recognition and experimentation, becoming gifts from third-party brands. The objective of the present study is to understand the perceptions of consumers in relation to the masstige brands presented and to understand the associations made when such brands are involved in promotional actions. To achieve the proposed objectives, we used a qualitative methodology with semi-structured interviews and the research sought out consumers of masstige brands and residents in Brazil. The sample consisted of 20 respondents, the field study was carried out between March and April 2022 and the data were analyzed through content analysis. The survey results show that the most recognized attributes of masstige brands are quality, status and prestige. As for the promotional actions, they are considered an incentive to increase the average purchase price and allow the experimentation of the brand and product by a lay public. The study also provides evidence that when the gift brand has a perceived prestige similar to the donor brand, consumers rated the action positively and were interested in participating and when there is a significant discrepancy in the prestige, quality or audience of the brands, there is impartiality in the consumer's judgment or the donor brand is negatively affected, reinforcing the need for symmetry in certain characteristics of the masstige brand of the gift and the donor brand. It is concluded that the findings of the present research contribute to the literature and the market, exposing the main attributes of the masstige brands presented and the consumer's perception of promotional actions with gifts.